2020
DOI: 10.1007/s12975-020-00818-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Stroke

Abstract: The COVID-19 pandemic is associated with neurological symptoms and complications including stroke. There is hypercoagulability associated with COVID-19 that is likely a "sepsis-induced coagulopathy" and may predispose to stroke. The SARS-CoV-2 virus binds to angiotensin-converting enzyme 2 (ACE2) present on brain endothelial and smooth muscle cells. ACE2 is a key part of the renin angiotensin system (RAS) and a counterbalance to angiotensin-converting enzyme 1 (ACE1) and angiotensin II. Angiotensin II is proin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
342
0
38

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(388 citation statements)
references
References 25 publications
8
342
0
38
Order By: Relevance
“…While the role of anticoagulation, like LMWH, in this clinical context is still unclear. [57] Harzallah et al recommended early anticoagulation therapy for individuals with COVID-19 infection and positive lupus anticoagulant. [58] Previous investigations suggested that COVID-19 is associated with both platelet and clotting cascade activation.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of anticoagulation, like LMWH, in this clinical context is still unclear. [57] Harzallah et al recommended early anticoagulation therapy for individuals with COVID-19 infection and positive lupus anticoagulant. [58] Previous investigations suggested that COVID-19 is associated with both platelet and clotting cascade activation.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulopathy induced by severe COVID-19 may lead to stroke [2]. Most reported cases present with respiratory symptoms initially, followed by stroke several days later [2,3]. However, we present a case of asymptomatic COVID-19 in an 84-year-old woman, who presented with stroke.…”
Section: Introductionmentioning
confidence: 84%
“…The unique feature of our case was that stroke occurred before the presentation of any other symptoms of COVID-19. According to the literature, coagulopathy occurs as a severe complication of COVID-19 [1,2,3]. However, in the study of Fara et al, coagulopathy may occur even in mild cases [6].…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations